Iberian vistas: Franco, Salazar, and American conservatives - Zúquete, José Pedro (2024)
The article takes both a historical and a present-oriented look at the influence of the twentieth century authoritarian Iberian regimes—including their leaders, Franco and Salazar—on the American conservative movement. It explores the political and religious motivations and major narratives driving Hispanophilia and Lusophilia, and their main advocates. Furthermore, and with a comparative approach, the text analyzes the past and current arguments—in magazines, books, and social media—favoring both regimes, especially in the light of the revival within American conservatism of Catholic Integralism and the defense of alternative representative systems, such as corporatism, that could usher in a new postliberal political regime. The article further explores the potential impact—and inherent limitations—of such strategies and projects, and shows that the revival of interest in figures such as Franco and Salazar is significant not only in terms of a reinvigorated criticism of the political and moral philosophy of liberalism but also regarding the search for new political forms and regimes.